Influence Marketing Mix and Behavior Entrepreneurship Against Sales Volume (Study Case Food City Courtyard of the Grand Mosque in the Soppeng District): - Nurul Arfianti Arib; Mustari Mustari; Muhammad Hasan (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2023)
This finding aims to determine the effect of marketing mix and entrepreneurial behavior on the study of sales volume at the food city courtyard of the grand mosque, Soppeng District. The method in its findings is a quantitative method by collecting observational data, questionnaires, and documentation. The number of samples is 24 respondents with multiple linear regression analysis. The findings illustrate that the simultaneous test of three variables (X) on Soppeng District business actors has a jointly significant effect on sales volume (Y) at the food city courtyard of the grand mosque of Soppeng District. Partially, the marketing mix variable (X1) has a positive and significant effect on sales volume (Y). Partially the entrepreneurial behavior variable (X2) has a positive and significant effect on sales volume (Y).